Dynamics of E-Learning During the Pandemic at Higher Education Institutions in Papua - Suratni, Suratni; Muhammad, Rivaldhy N.; S, Lestari Wulandari; Qomarrullah, Rif'iy; Sawir, Muhammad (Journal of Education Technology, 2022)
Covid-19 has had a significant impact on the teaching and learning process. This study aims to evaluate the teaching and learning process during the pandemic, the interesting and different thing is that this research is carried out in online learning in Papua. This study uses a qualitative descriptive method, the research subjects are students and lecturers in Papua, Indonesia. This research was conducted through three stages, namely: data collection; data reduction; and verification and confirmation of conclusions. The instruments used are interviews, photo documentation through the Whatsapp application. Data analysis in this study used the triangulation method (measurement of data validity). The results of this study are: First, e-learning during the pandemic is difficult to run well, this is influenced by facilities such as networks and communication devices; Second, the impact of e-learning is that the emotional closeness between lecturers and students is not well established, learning is monotonous and there are more tasks in the form of orders; Third, e-learning provides benefits, namely forcing the acceleration of mastery of digital-based learning technology in Papua, social media content is used more massively. The conclusion of this research is that there are various opinions of lecturers and students in e-learning during the pandemic, starting from the infrastructure, the quality of the interaction, and the benefits received. The impact of this research is the importance of further increasing the development of development facilities, especially to support the improvement of education in Papua, and special handling to advance Eastern Indonesia.